Greater ectopic fat deposition and liver fibroinflammation and lower skeletal muscle mass in people with type 2 diabetes. Issue 6 (27th April 2022) - Waddell, Tom; Bagur, Alexandre; Cunha, Diogo; Thomaides‐Brears, Helena; Banerjee, Rajarshi; Cuthbertson, Daniel J.; Brown, Emily; Cusi, Kenneth; Després, Jean‐Pierre; Brady, Michael
Abstract: Objective: Type 2 diabetes (T2D) is associated with significant end‐organ damage and ectopic fat accumulation. Multiparametric magnetic resonance imaging (MRI) can provide a rapid, noninvasive assessment of multiorgan and body composition. The primary objective of this study was to investigate differences in visceral adiposity, ectopic fat accumulation, body composition, and relevant biomarkers between people with and without T2D. Methods: Participant demographics, routine biochemistry, and multiparametric MRI scans of the liver, pancreas, visceral and subcutaneous adipose tissue, and skeletal muscle were analyzed from 266 participants (131 with T2D and 135 without T2D) who were matched for age, gender, and BMI. Wilcoxon and χ 2 tests were performed to calculate differences between groups. Results: Participants with T2D had significantly elevated liver fat (7.4% vs. 5.3%, p = 0.011) and fibroinflammation (as assessed by corrected T1 [cT1]; 730 milliseconds vs. 709 milliseconds, p = 0.019), despite there being no differences in liver biochemistry, serum aspartate aminotransferase ( p = 0.35), or alanine transaminase concentration ( p = 0.11). Significantly lower measures of skeletal muscle index (45.2 cm 2 /m 2 vs. 50.6 cm 2 /m 2, p = 0.003) and high‐density lipoprotein cholesterol (1.1 mmol/L vs. 1.3 mmol/L, p < 0.0001) were observed in participants with T2D. Conclusions: Multiparametric MRI revealed significantly elevated liver fat and fibroinflammation in participants with T2D, despite normal liver biochemistry. This study corroborates findings of significantly lower measures of skeletal muscle and high‐density lipoprotein cholesterol in participants with T2D versus those without T2D.